2016
DOI: 10.1371/journal.pone.0164084
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Serum Ferritin before and after Bariatric Surgery: Analysis in Dentate and Edentulous Patients

Abstract: Society has changed its own lifestyle, specially its eating habits and physical activities, leading to excessive weight and a sedentary behavior, which has contributed to obesity increase. Bariatric surgery is the most effective treatment to obesity, allowing weight loss and its maintenance. However, it has been related high levels of iron deficiency after surgery. A person’s nutritional status might be affected by total or partial tooth loss. The aim of this longitudinal prospective cohort study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 99 publications
0
8
0
6
Order By: Relevance
“…In this study, a higher prevalence of hypertension was observed in patients with obesity ( P = .020) (Table 1). Hypertension was the most important risk factor for cardiovascular disease, being more common than smoking, dyslipidemia, and diabetes 2,18,19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a higher prevalence of hypertension was observed in patients with obesity ( P = .020) (Table 1). Hypertension was the most important risk factor for cardiovascular disease, being more common than smoking, dyslipidemia, and diabetes 2,18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with obesity have a reduced immune response considering the widespread inflammatory state of the body caused by inflammatory cytokines and adipokines, including tumor necrosis factor alpha (TNF‐α), Interleukin‐6 (IL‐6), adiponectin, leptin, adipocytokine, and cytoplasmic enzymes 1 . These patients may present several comorbidities, such as hypertension, dyslipidemia, type II diabetes mellitus, and obstructive sleep apnea 2 . Furthermore, obesity has been associated with several oral changes, including reduced salivary flow, periodontal diseases, and tooth loss 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O estado nutricional de um individuo pode ser afetado pela perda total ou parcial dos dentes. Foratori et al, 2016 avaliaram os níveis de ferritina sérica antes e apos a cirurgia bariátrica e obtiveram como resultado que após a cirurgia, os níveis de ferritina sérica foram maiores em pacientes edêntulos quando comparados com os pacientes pré-cirurgia bariátrica.…”
Section: Perdas Dentárias Entre Os Indivíduos Obesos Hipertensos (G01unclassified
“…Fato este, que deveria contribuir para a redução da periodontite, o que não ocorre. Tendo em vista o aumento no número de P. gingivalis e do sangramento periodontal (SALES-PERES et al, 2016), após a cirurgia bariátrica.…”
Section: Implicações Clínicasunclassified